The Impact of Digital Transformation on the Strategic Management of PT. Matahari Department Store Tbk. Jakarta Period 2016–2025 - Supriyadi, Supriyadi; Firmansyah, Firmansyah (Journal of Industrial Engineering & Management Research, 2026)
The rapid development of digital technology has forced companies in the retail sector to transform their business models and strategic management practices. PT. Matahari Department Store Tbk., as one of Indonesia’s largest retail companies, has implemented various digital transformation initiatives to remain competitive in an increasingly dynamic market (Todorescu et al., 2014). This study aims to analyze the impact of digital transformation on the strategic management of PT. Matahari Department Store Tbk. during the period 2016–2025. The research uses a qualitative descriptive approach by examining company reports, strategic policies, and secondary data related to digital innovation. The results indicate that digital transformation has significantly influenced strategic decision-making, operational efficiency, customer engagement, and long-term competitiveness. The study concludes that digital transformation is a critical factor in strengthening strategic management and sustaining business growth in the retail industry.